Does Reentry Court Completion Affect Recidivism Three Years after Exit? Results from a Retrospective Cohort Study. Issue 4 (8th August 2021) - Lawson, Spencer G.; Grommon, Eric; Ray, Bradley
ABSTRACT: Reentry courts are a strategy to assist individuals subjected to post-release supervision in the reintegration process, but there is limited evidence on the effectiveness of these practices. The current study presents the results of a retrospective cohort study for a sample of 340 participants who exited a reentry court. Specifically, survival analyses were employed to evaluate whether participants' reentry court completion status affects their likelihood of and timing to recidivism events three years after exiting the program. The results revealed that successful program completion continues to shape recidivism outcomes up to three years after reentry court exit.